Proxy analysis of hospital admissions due to colorectal cancer and Schistosoma mansoni incidence - Almeida, Gustavo Fernandes Godoy; Freitas, Mauricio Assuero Lima de; Ribeiro, Lais Neares Barbosa; Lira, Mariana Montenegro de Melo; Moura, Maxwell Alex de Lima; Silva, Lauro Vinicius Machado da; Mattos, Luiz Alberto Reis, Jr; Domingues, Ana Lucia Coutinho (Brazilian Journal of Oncology, 2018)
Schistosoma has been associated with colorectal cancer. We compared the number of colorectal cancer admissions between those cities in the state of Pernambuco with and without schistosomiasis. We abstracted data from Datasus and analyzed the number of admissions due to CRC in those cities with (CRC/Schistosoma) and without schistosomiasis (CRC-alone) in the State of Pernambuco and compared these numbers using odds ratio and relative risk at a significance level of 5%. This was preceded by an F test to reject the null hypothesis that the number of cities in each group was the same. The mean number of admissions due to CRC in CRC-Schistosoma cities was 94.55, with a variability of 366%, while in CRC-alone cities the mean was 11.06, with a variability of 88%. A test at a significance level of 5% rejected the hypothesis that these variances were the same (p-value, 0.0000). A subsequent test also rejected the null hypothesis that the mean of admissions was the same (two-sided p-value 0.0167). The state of Pernambuco encompasses 184 cities of which 103 registered schistosomiases (102 with colorectal cancer and 1 without). We compared the number of admissions due to CRC and/or due to schistosomiasis with admissions due to other diseases to measure the odds ratio for colorectal cancer due to schistosomiasis exposure. This comparison resulted in an OR of 2.657 (CI 95% 2,478-2,849) for CRC due to exposure to schistosomiasis. We found a statistically significant correlation between colorectal cancer admissions and schistosomiasis in the state of Pernambuco. Pharmacoeconomic studies might proof if investment to prevent nematode infestation would translate into cost spare with less admissions due to cancer and cancer treatments.
Keywords: Schistosoma; Schistosoma mansoni; Colorectal Neoplasms; Carcinogenesis; Patient Admission